Generalization over Environments in Reinforcement Learning - Matt, Andreas (2002)
In this paper we discuss the problem of reinforcement learning in one environment and applying the policy obtained to other environments. We first state a method to evaluate the utility of a policy. We then propose a general model to apply one policy to different environments and compare them. To illustrate the theory we present examples for an obstacle avoidance behavior in various block world environments.